KEY PERFORMANCE INDICATORS AND ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW OF FRAMEWORKS, IMPLEMENTATION, AND HUMAN RESOURCE MANAGEMENT IMPLICATIONS - R. Muh. Deddy Hanif Sardjito; Herry Prinada; Cedaryana Cedaryana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This systematic literature review synthesizes extant research on Key Performance Indicators (KPIs) and organizational performance. Following PRISMA 2020 guidelines and the PICOC framework, a systematic search was conducted across Scopus, Web of Science, and Emerald Insight databases. Applying structured inclusion/exclusion criteria and quality appraisal using a modified Critical Appraisal Skills Programme (CASP) checklist, 43 peer-reviewed studies published between 2021 and 2026 were included in the final synthesis. Thematic synthesis identified five overarching themes: (1) KPI Framework Design and Methodological Foundations; (2) KPI Culture, Communication, and Organisational Adoption; (3) Technology-Enabled KPI Monitoring and Analytics; (4) Cross-Sectoral KPI Applications and Contextual Adaptation; and (5) HRM-KPI Integration and People Performance Management. Findings reveal that while technology-enabled KPI systems have advanced rapidly, organisational culture, employee awareness, and leadership communication remain persistent barriers to effective implementation. The review proposes the Integrated KPI-Performance Framework (IKPF) bridging measurement design, organisational culture, and digital enablement. Organisations should invest simultaneously in robust KPI systems and a culture of performance transparency and accountability.